Stocking rate and capital indicators in extensive sheep farms (sw spain) (Arch. Zootec, 2002)
The animal production systems in the SW of the Iberian Peninsula are characterized by extensive livestock farming. The data for the present study were collected by survey in the year 2000 from 96 dehesa sheep farms in Extremadura. We studied the stocking rate effects on a number of capital indicators for each farm. The data were analysed for three stocking rate levels: low (<0.25 UGM/ha), medium (0.25-0.5 UGM/ha), and high (0.5 UGM/ha). The differences were compared by analysis of variance, following the GLM procedure.